Metal-ligand interactions in a redox active ligand system. Electrochemistry and spectroscopy of [M(dipyvd)2]n+ (M=Zn, Ni, n=0, 1, 2) - Fleming, Connor; Vu, Son; Brook, David J. R.; Agrestini, Stefano; Pellegrin, Eric; DaRos, Jeffrey (Frontiers in Chemistry, 2023)
Reaction of nickel and zinc triflates with the tridentate leucoverdazyl 1-isopropyl-3,5-di(2′-pyridyl)-6-oxo-2H-tetrazine (dipyvdH) and triethylamine resulted in the neutral coordination compounds M(dipyvd)2 (M=Ni,Zn). In acetonitrile, both compounds undergo two one electron oxidation processes, Zn(dipyvd)2 at -0.28V and -0.12V and Ni(dipyvd)2 at -0.32V and -0.15V vs. ferrocene/ferricenium. Oxidations are ligand based resulting in an intermediate mixed valence species and a cationic bis(verdazyl) compound respectively. Oxidation of the ligand changes a localized, antiaromatic, non-planar 8π electron anion to a planar, delocalized 7π electron radical. The change in ligand structure results in an increase in the octahedral ligand field splitting from 10500 cm -1 to 13000 cm -1 , suggesting an increase in the pi acceptor character of the ligand. In the mixed valence species, spectroscopic data suggests minimal interaction between ligands mediated by the metal center; i.e. these are class I-II systems in the Robin-Day classification.